2018
DOI: 10.31234/osf.io/xr2vf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On Non-Regularized Estimation of Psychological Networks

Abstract: An important goal for psychological science is developing methods to characterize relationships between variables. The customary approach uses structural equation models to connect latent factors to a number of observed measurements. More recently, regularized partial correlation networks have been proposed as an alternative approach for characterizing relationships among variables through covariances in the precision matrix. While the graphical lasso (glasso) method has merged as the default network estimatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Given the effort invested in estimating the network structure, it is a missed opportunity not to use the information it entails more fully to gain deeper understanding of estimated network. This "omission" may be understood and partly explained by researchers in the field being preoccupied primarily with network estimation methods [11,47,62] and replicability issues [49,63,64] that arise from the fact that network structures between variables are considerably more difficult to determine, relative to, for example, internet links or electricity nets; after all, conditional association between variables is not observable, but must be estimated from data. Appropriately dealing with sampling error in estimating network structures, as well as assessing their robustness, has therefore been the priority in psychological network analysis.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the effort invested in estimating the network structure, it is a missed opportunity not to use the information it entails more fully to gain deeper understanding of estimated network. This "omission" may be understood and partly explained by researchers in the field being preoccupied primarily with network estimation methods [11,47,62] and replicability issues [49,63,64] that arise from the fact that network structures between variables are considerably more difficult to determine, relative to, for example, internet links or electricity nets; after all, conditional association between variables is not observable, but must be estimated from data. Appropriately dealing with sampling error in estimating network structures, as well as assessing their robustness, has therefore been the priority in psychological network analysis.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Partial correlation networks do not contain spurious correlations that are generated by common cause and chain structures within the network and can encode a basic data-generating network structure [46]. To estimate the network, we used a nonregularized method recently proposed by Williams and Rast (in press) [47] because, given our large sample size, relatively small number of variables, and our interest to detect weak ties, it is not advised to use regularization techniques like the LASSO that are often used ( [47,48], in press). More details about the process of determining the optimal estimation method for our data, and about the nonregularization method used, can be found in SM, Section 5.…”
Section: Network Estimationmentioning
confidence: 99%
“…The EBIC itself has a tuning parameter gamma, which we set to 0 for the main models in the paper (see Supplementary Materials for a detailed rationale). As recommended in recent literature, we also estimated the final model without any regularization (Williams et al 2019) whilst still controlling for the false positive rate. We also estimated node predictability, which quantifies how well a node can be predicted by nodes it shares an edge with.…”
Section: Network Estimationmentioning
confidence: 99%
“…The Gaussian graphical model (GGM) has become increasingly popular in the social-behavioral sciences (Epskamp Research reported in Williams, Rhemtulla, Wysocki, & Rast, 2018). Traditional statistical approaches, for example the structural equation model (SEM) framework, conceptualize psychological constructs as arising from a common cause (i.e., latent variable; Cramer & Borsboom, 2015).…”
Section: Introductionmentioning
confidence: 99%